2018
DOI: 10.1111/jpc.13931
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin and C‐reactive protein as biomarkers for neonatal bacterial infection

Abstract: Further research is required before definitive recommendations can be made about the utility of procalcitonin compared with CRP as a diagnostic marker for neonatal sepsis and bacterial infection in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Perhaps one of the most hotly debated acute phase reactants, procalcitonin, is the latest diagnostic darling in inpatient circles. Procalcitonin (the biologic precursor to calcitonin) reaches measurable serum concentrations quickly and reliably in the setting of bacterial infection 27–29. Dozens of trials have reliably demonstrated procalcitonin’s strong performance in decision support for antibiotic initiation or cessation; however, in the most salient ED investigation—the Procalcitonin Consensus Trial (ProACT) —procalcitonin failed miserably in limiting unnecessary antibiotic use 30.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps one of the most hotly debated acute phase reactants, procalcitonin, is the latest diagnostic darling in inpatient circles. Procalcitonin (the biologic precursor to calcitonin) reaches measurable serum concentrations quickly and reliably in the setting of bacterial infection 27–29. Dozens of trials have reliably demonstrated procalcitonin’s strong performance in decision support for antibiotic initiation or cessation; however, in the most salient ED investigation—the Procalcitonin Consensus Trial (ProACT) —procalcitonin failed miserably in limiting unnecessary antibiotic use 30.…”
Section: Resultsmentioning
confidence: 99%
“…PCT is a protein, which increased in the SSI patients (OR = 220.746, P < 0.05). Its levels in the plasma rose in severe bacterial, fungal and parasitic infections as well as sepsis [28]. Bacterial endotoxin played an important role in the induction process [29].…”
Section: Discussionmentioning
confidence: 99%
“…Blood culture remains the gold standard for the diagnosis of neonatal sepsis, but results are delayed and have low sensitivity due to maternal antibiotic treatment, small sample volumes, and low bacteremia 18,19 . Other tests routinely used for the diagnosis of neonatal sepsis, such as C-reactive protein (CRP) and blood count (total and differential white blood cell counts, absolute and immature neutrophil counts, and the ratio of immature to total neutrophils), are respectively non-speci c and non-sensitive [20][21][22][23] . Procalcitonin (PCT) has been shown to be an excellent marker for severe bacterial infection in newborn [24][25][26] .…”
Section: Introductionmentioning
confidence: 99%